Thermally tuned TeO2-Si Microdisk Resonators - Edke, Parimal (My University, 2022)
In this research, we design and characterize thermally tuned hybrid tellurium ox- ide coated silicon (TeO2-Si) microdisk resonators for the development of tunable on chip lasers. Several heater designs are proposed that are compatible with stan- dard silicon photonics foundry processes and the requirement to deposit TeO2 onto the fabricated chips in post-processing. The devices are designed using simulation software packages such as Lumerical MODE and HEAT to simulate the mode profiles and thermo-optic coefficients of the microdisk resonators and the heating profiles of the various heater designs. The devices are laid out using the Luceda IPKISS Photonics Design Platform and fabricated at the AMF silicon photonics foundry. TeO2 is then deposited onto the fabricated chips at McMaster University in a single post-processing step via reactive radio frequency magnetron sputter- ing. Passive optical transmission measurements are performed to characterize the intrinsic Q-factors, loss and FSR of the microdisks. This is followed by resonance tuning measurements to characterize the tuning efficiencies of each of the heater designs presented in this thesis. The performances of each of the heater designs are then discussed and compared.
Keywords: Silicon Photonics